Effectiveness of herbal medicine for liver cancer treatment as revealed by a bibliometric and visualization analysis - Shi, Yusha; Wang, Juwei; Zhang, Yahui; Wu, Kai; Zhu, Yibo; Yan, Kaiwen; Ouyang, Qin (Frontiers in Oncology, 2025)
BackgroundLiver cancer is highly prevalent worldwide. However, current medical treatments remain insufficient. Although herbal medicine has a long history and extensive expertise in treating liver cancer, the literature in this field has not been thoroughly explored. This study aims to assess and analyze the distribution patterns and key research areas of publications concerning herbal medicine for liver cancer.MethodsLiterature on herbal medicine and liver cancer published between January 1, 2008, and September 28, 2024, was collected for this research. Excel, CiteSpace 6.4.R1, VOSviewer 1.6.20, Scimago Graphica, and Bibliometrix 4.1 were used for data analysis.ResultThe study examines 634 academic articles on herbal medicine for liver cancer, with the majority contributed by Chinese researchers, particularly from Shanghai University of Traditional Chinese Medicine. Wang Ning is the most productive author, possessing the highest h-index. The JOURNAL OF ETHNOPHARMACOLOGY has the most publications and the highest h-index. Journals publishing on herbal medicine and liver cancer are primarily in the fields of molecular biology and immunology, whereas the cited journals are mainly in the fields of environment, toxicology, and nutrition. Keyword clustering analysis indicates that “NF kappa B” and apoptosis have long been the main research topics in this field. Analysis of emergent words suggests that “network pharmacology”, antioxidants, “adjuvant therapy”, and “molecular docking” may become significant research topics in the near future.ConclusionThis analysis provides a comprehensive overview of the current status, primary focuses, and emerging trends in research related to herbal medicine and liver cancer.